Assessment of behavioral, neuroinflammatory, and histological responses in a model of rat repetitive mild fluid percussion injury at 2 weeks post-injury - Fronczak, Katherine M.; Roberts, Andrea; Svirsky, Sarah; Parry, Madison; Holets, Erik; Henchir, Jeremy; Dixon, C. Edward; Carlson, Shaun W. (Frontiers in Neurology, 2022)
Repetitive mild traumatic brain injury (rmTBI) is a prominent public health concern, with linkage to debilitating chronic sequelae. Developing reliable and well-characterized preclinical models of rmTBI is imperative in the investigation of the underlying pathophysiological mechanisms, as models can have varying parameters, affecting the overall pathology of the resulting injury. The lateral fluid percussion injury (FPI) model is a reliable and frequently used method of TBI replication in rodent subjects, though it is currently relatively underutilized in rmTBI research. In this study, we have performed a novel description of a variation of the lateral repetitive mild FPI (rmFPI) model, showing the graded acute behavioral impairment and histopathology occurring in response to one, two or four mild FPI (1.25 atm) or sham surgeries, implemented 24h apart. Beam walking performance revealed significant motor impairment in injured animals, with dysfunction increasing with additional injury. Based upon behavioral responses and histological observations, we further investigated the subacute pathophysiological outcomes of the dual FPI (dFPI). Immunoreactivity assessments showed that dFPI led to regionally-specific reductions in the post-synaptic protein neurogranin and increased subcortical white matter staining of the presynaptic protein synaptophysin at 2 weeks following dFPI. Immunohistochemical assessments of the microglial marker Iba-1 showed a striking increase in in several brain regions, and assessment of the astrocytic marker GFAP showed significantly increased immunoreactivity in the subcortical white matter and thalamus. With this study, we have provided a novel account of the subacute post injury outcomes occurring in response to a rmFPI utilizing these injury and frequency parameters, and thereby also demonstrating the reliability of the lateral FPI model in rmTBI replication.